Saccharin: A lead compound for structure-based drug design of carbonic anhydrase IX inhibitors. Issue 4 (15th February 2015) - Mahon, Brian P.; Hendon, Alex M.; Driscoll, Jenna M.; Rankin, Gregory M.; Poulsen, Sally-Ann; Supuran, Claudiu T.; McKenna, Robert
Graphical abstract: Abstract: Carbonic anhydrase IX (CA IX) is a key modulator of aggressive tumor behavior and a prognostic marker and target for several cancers. Saccharin (SAC ) based compounds may provide an avenue to overcome CA isoform specificity, as they display both nanomolar affinity and preferential binding, for CA IX compared to CA II (>50-fold forSAC and >1000-fold whenSAC is conjugated to a carbohydrate moiety). The X-ray crystal structures ofSAC and a SAC-carbohydrate conjugate bound to a CA IX-mimic are presented and compared to CA II. The structures provide substantial new insight into the mechanism ofSAC selective CA isoform inhibition.